PESANTREN: ANTARA ORIENTALISME DAN OKSIDENTALISME - Nuril Hidayah (LPPM STAI Muhammadiyah Probolinggo, 2019)
From modern perspective, pesantren are often regarded as the basis of resistance to modernization that is often associated with the West. This resistance comes from the strong roots of the pesantren as a subculture. This study attempts to elaborate on how the pesantren's view of the West as a part of occidentalism. Using literary sources and content analysis methods, this study has resulted several conclusions. First, in the pre-independence era where the West was represented by the Dutch, The West had a bad image among the pesantrens. The Dutch was viewed as invaders who exploit people and stab them from behind. In addition, with public schools filled with aristocrats, the Netherlands became a competitor to civil education which was rooted in community based pesantren education. On the other hand, from the standpoint of religion, pesantren viewed the West as infidels